The Role of The Family in Shaping Social and Domestic Readiness - Anvarova Dilfuza Akramjanovna (European International Journal of Pedagogics, 2026)
This article highlights the role of the family in the formation of socio-domestic readiness, the educational responsibility of parents, and the importance of family and school cooperation. The functions of the family as the main social environment in the formation of the child's personality are analyzed based on scientific and pedagogical sources. The article also broadly reveals the principles of moral education, the influence of the spiritual environment in the family on the child's behavior, socialization, and readiness for independent life. The views of such thinkers as Abu Ali Ibn Sina, Kaykovus, Mirzo Ulugbek on family education, as well as the scientific approaches to socialization of modern pedagogical and psychological scientists, are analyzed. The author substantiates that the presence of love, mutual respect, cooperation, and a positive psychological environment in the family are important factors in the child's successful acquisition of socio-domestic skills. The article emphasizes the great importance of the personal example of parents in the formation of moral qualities, self-confidence, initiative and social adaptation, especially in children of primary school age. It also highlights the fact that the right educational environment created in the family serves as an important pedagogical basis for children's adaptation to future society, industriousness, spiritual maturity and readiness for independent life.